Implementasi Model Quick on The Draw Untuk Meningkatkan Keterampilan Kerja Sama Siswa dalam Pembelajaran Akidah Akhlak di Madrasah - Laili, Pai Datul; Hartati, Zainap; Hikmah, Nurul (Kamaya: Jurnal Ilmu Agama, 2025)
The low participation and contribution of students in group discussions result in a lack of cooperation among them. The purpose of this study was to improve the collaborative skills of XI MA Darul Ulum Palangka Raya students by applying the quick on the draw learning model. This research used a classroom action research (CAR) method. The findings of this study indicated that many students needed encouragement to actively participate, as the research found that their average score for cooperation skills reached 54% in the first cycle. Teamwork abilities improved significantly during the second cycle, with the average score rising to 81%, a 27% improvement compared to the first cycle. Students began to cooperate better, showing appreciation for others' efforts, taking turns and sharing responsibilities, respecting others' differences, staying in their groups during activities, and completing work on time, according to the findings. Additionally, the number of students falling into the “Very Good” category increased from 12 in the third meeting to 23 in the fourth meeting, demonstrating substantial progress.